Sintesis Nanopartikel Perak Menggunakan Ekstrak Daun Eceng Gondok (Eichornia crassipes) Sebagai Bioreduktor: Synthesis of Silver Nanoparticles Using Leaves Extract of Water Hyacinth (Eichornia crassipes) As a Bioreductor - Syahruddin Kasim; Paulina Taba; Ruslan; Romi Anto (KOVALEN: Jurnal Riset Kimia, 2020)
Nanoparticles was done by adding water hyacinth leave extract to AgNO3 2mM solution with a ratio of 1:40. Formed silver nanoparticles were analyzed using UV-Vis spectrophotometer, SEM, XRD, PSA, and FTIR to determine its characteristics. Results showed that absorbance value increased if reaction time is increased. Maximum absorption was obtained at wavelength 432-446 nm by using UV-Vis spectrophotometer. Result of PSA analysis shows that the average size of silver nanoparticles formed is 93.2 nm while XRD analysis shows that the average crystal size of silver nanoparticles is 50.11 nm, with round shape and amorphous. Result of FTIR analysis to determine functional group that contributes to nanoparticle synthesis shows the contribution of OH group. Keywords: reduction method, silver nanoparticles, Eichornia crassipes, bioreductor